Daily Life, Materiality, and Complexity in Early Urban Communities of the Southern Levant Papers in Honor of Walter E. Rast and R. Thomas Schaub - Bar-Yosef Mayer, Daniella E.; Braun, Eliot; Chesson, Meredith S.; Chesson, Meredith S.; Dever, William G.; Douglas, Khaled; Fischer, Peter M.; Frohlich, Bruno; Greenberg, Raphael; Harrison, Timothy P.; Kafafi, Zeidan A.; Kerner, Susanne; et al. (Penn State University Press, 2021)
This volume emerges from a session honoring Walter E. Rast and R. Thomas Schaub held during the 2003 Annual Meeting of the American Schools of Oriental Research in Atlanta, Georgia and includes expanded versions of many of the papers presented in that session. By gathering in Atlanta, and by participating in this volume, the contributors honor the careers and scholarly passions of Walt and Tom, whose work in southern Levantine archaeology began in the 1960s when they were young scholars working with Paul Lapp. The breadth and depth of experience of the contributors' disciplinary and theoretical interests reflects the shared influence of and esteem for Walt's and Tom's own scholarly gifts as archaeologists, mentors, collaborators, and intellectual innovators.